The Influence of Zakat Fund Management and Zakat Fund Distribution on Poverty Levels at Baznas Palembang City - Abubakar Sidik; Marlina, Ema (Jurnal I-Philanthropy, 2025)
This study aims to analyze the influence of zakat fund management and zakat fund distribution on poverty levels in BAZNAS Palembang City. Zakat as an Islamic economic instrument has significant potential in reducing poverty if managed and distributed effectively. The method used in this study is quantitative through the distribution of questionnaires aimed at mustachio baznas Palembang city. The sample used was 99 respondents from the calculation of the Slovin formula and using purposive sampling technique, the data obtained were then processed using the SPSS version 26 application, the types of data in this study were primary data and secondary data, data analysis used included validity testing, classical assumption testing, multiple linear regression testing and hypothesis testing. The results of the study indicate that the zakat fund management variable (X1) has an effect on the poverty rate at BAZNAS Palembang City with a significant value of the zakat fund management variable of 0.00 <0.05 with a calculated t value <t table (-9.802 <1.660). The zakat fund distribution variable has an effect on the poverty rate at BAZNAS Palembang City with a significant level of the zakat fund distribution variable of 0.00 smaller than 0.05 with a calculated t value <t table (-10.004 <1.660). The results of the study are expected to provide benefits for BAZNAS Palembang City mustahik in using zakat funds with the management and distribution of zakat funds